The Role of Teachers in the Implementation of the ADDIE Model in Islamic Religious Education Learning - Mulyawan Safwandy Nugraha; Retno Dwi Ramadhannita; Ujang Dedih (al-Afkar, Journal For Islamic Studies, 2024)
Each student has a different level of understanding and needs in understanding religious teachings. Therefore, the learning design should consider the specificity and depth of this material. Learning Islamic Religious Education is not only about understanding theoretical concepts, but also about the experience and appreciation of religious character values. There are many learning models that teachers in classroom learning can apply. One of them is the ADDIE model. The use of the ADDIE model is relevant and flexible to use because of its ability to adapt well to various situations. The purpose of this study is to find out how much the teacher's role in learning by using the ADDIE model. The researcher adopted a qualitative approach within a descriptive research framework. The results of the study show that teachers have a very important role in the implementation of the ADDIE model in Islamic learning. Through the ADDIE model, teachers can ensure that the learning process runs well, effectively and efficiently. Especially in the field of Al-Qur'an in Islamic Religious Education subjects.